Confirmatory Factor Analysis of Three Versions of the Depression Anxiety Stress Scale (DASS-42, DASS-21, and DASS-12) in Polish Adults - Makara-Studzińska, Marta; Tyburski, Ernest; Załuski, Maciej; Adamczyk, Katarzyna; Mesterhazy, Jacek; Mesterhazy, Agnieszka (Frontiers in Psychiatry, 2022)
Background: The Depression Anxiety Stress Scales (DASS) are designed to identify quickly and differentiate between the symptoms of depression and anxiety in the non-clinical population. Different versions (original and short) were validated in many cultures. Nevertheless, there is no data of factorial validity of the different versions of this scale in Polish culture. Thus, the aim of this study was to evaluate the factor structure using confirmatory factor analysis (CFA) and internal consistency of DASS-42 (original version) and two short versions (DASS-21 items and DASS-12 items) in the Polish population. Methods: The DASS-42 was administered to a non-clinical sample, broadly representative of the general Polish adult population (n = 1021) in terms of demographic variables. The DASS-21 and DASS-12 version used in this study comprise seven and four items from each of the following corresponding three subscales of the Polish version of DASS-42. Results: There were two models that fitted best for DASS-42: (a) modified three correlated factors (depression, anxiety, and stress) with cross loadings and (b) second order (general factor of psychological distress) and three factors with cross loadings. There also were two models that fitted best for DASS-21 and DASS-12: (a) modified three correlated factors (depression, anxiety, and stress) and (b) second order (general factor of psychological distress) and three factors. Conclusions: All three versions of DASS appear to have an acceptable factorial structure. However, the shorter versions (DASS-21 and DASS-12) may be more feasible to use in general medical practice and also be less burdensome to participants.